ChemInform Abstract: The Synthesis of Pyrroles and Oxazoles Based on Gold α‐Imino Carbene Complexes. Issue 40 (16th September 2016) - Loy, Nicole S. Y.; Choi, Subin; Kim, Sunggak; Park, Cheol‐Min
Abstract: Cationic gold complexes of α‐oximimino carbenes react with weak nucleophiles including enol ethers and nitriles to provide the highly efficient synthesis of pyrroles and oxazoles.